(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
The internet is reshaping modern lives in communication by creating consistent communication patterns globally beating aspects of time and space; exploring the potential of platform ‘cooperativism’ would be paramount to its success in Kenya. Coops provide a platform for entrepreneurship, savings, among others. The objective of this research work is to explore the potential of platform cooperativism in Kenya.